2009
DOI: 10.1534/genetics.109.104174
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Recombination on Complex Regulatory Circuits

Abstract: Mutation and recombination are the two main forces generating genetic variation. Most of this variation may be deleterious. Because recombination can reorganize entire genes and genetic circuits, it may have much greater consequences than point mutations. We here explore the effects of recombination on models of transcriptional regulation circuits that play important roles in embryonic development. We show that recombination has weaker deleterious effects on the expression phenotypes of these circuits than mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
77
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(80 citation statements)
references
References 55 publications
3
77
0
Order By: Relevance
“…We documented two differences between sexual and asexual populations that likely affected the evolution of U d : First, sexual populations uniquely experienced recombination load, L R : We know from previous work that selection to minimize L R ; alone, results in increasing robustness to both recombination and mutation, lowering U d (Azevedo et al 2006;Gardner and Kalinka 2006;Misevic et al 2006;Martin and Wagner 2009;Lohaus et al 2010). Second, asexual populations uniquely experienced Hill-Robertson interference that reduced N e ( Figure 3B).…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…We documented two differences between sexual and asexual populations that likely affected the evolution of U d : First, sexual populations uniquely experienced recombination load, L R : We know from previous work that selection to minimize L R ; alone, results in increasing robustness to both recombination and mutation, lowering U d (Azevedo et al 2006;Gardner and Kalinka 2006;Misevic et al 2006;Martin and Wagner 2009;Lohaus et al 2010). Second, asexual populations uniquely experienced Hill-Robertson interference that reduced N e ( Figure 3B).…”
Section: Discussionmentioning
confidence: 87%
“…We found that Hill-Robertson interference also played a role in our model in creating both a longterm and a short-term advantage of sex. But we also showed that the long-and short-term advantages of sex were determined by differences between sexual and asexual populations in the evolutionary dynamics of two properties of the genetic architecture, U d and L R : We next sought to quantify the contribution of Hill-Robertson interference to these dynamics.We documented two differences between sexual and asexual populations that likely affected the evolution of U d : First, sexual populations uniquely experienced recombination load, L R : We know from previous work that selection to minimize L R ; alone, results in increasing robustness to both recombination and mutation, lowering U d (Azevedo et al 2006;Gardner and Kalinka 2006;Misevic et al 2006;Martin and Wagner 2009;Lohaus et al 2010). Second, asexual populations uniquely experienced Hill-Robertson interference that reduced N e ( Figure 3B).…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…Interestingly, this response might promote the maintenance of recombination through the more efficient elimination of deleterious mutations [20]. It was also found that circuits evolved with recombination were enriched for cis-regulatory complexes [12], and hence had an increased modular structure. Evolution experiments with digital organisms similarly found that recombination increased robustness and modularity, and reduced unidimensional epistasis [13].…”
Section: (D) Robustnessmentioning
confidence: 99%
“…In addition to extensive studies on mutational robustness and evolvability, it has been proposed recently in the context of gene regulatory circuits that recombination can create novel phenotypes more efficiently with a much less disruptive effect than mutation [20,33]. It is argued that recombination reorganizes genes and gene circuits and thus has greater phenotypic consequences than point mutation.…”
Section: Introductionmentioning
confidence: 99%